ANALISIS LITERASI KEUANGAN PADA MAHASISWA JURUSAN PENDIDIKAN EKONOMI DITINJAU BERDASARKAN GENDER - Kurniawan Kurniawan (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
This research was conducted to determine the level of financial literacy in students majoring in Economic Education at Siliwangi University, in terms of gender . The study was conducted through descriptive analytical methods using survey techniques . Data collection was carried out by distributing instruments in the form of questionnaires regarding financial literacy. The study population was students in 2013-2016, and samples were taken through proportionate random sampling techniques. Data analysis techniques were performed using descriptive statistics. The results showed financial literacy in female students was higher than male students. Keyword: Financial, Literacy, College, Student, Gender